2018
DOI: 10.3390/nu10070899
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of a Whey Peptide Rich in Tryptophan-Tyrosine-Related Peptides on Cognitive Performance in Healthy Adults: A Randomized, Double-Blind, Placebo-Controlled Study

Abstract: Background: Previous epidemiological and clinical studies have shown that dairy products have beneficial effects on cognitive decline and dementia. Enzymatic digestion of whey protein produces a whey peptide rich in tryptophan-tyrosine-related peptides which improve cognitive performance in mice. We evaluated the effects of whey peptides on cognitive functions in healthy adults in a randomized, double-blind, placebo-controlled design. Methods: 101 healthy adults (45 to 64 years), with a self-awareness of cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 29 publications
5
47
0
Order By: Relevance
“…Accumulating evidence [16,17] indicates that supplementation with whey digestion rich in ␤-lactolin improves memory retrieval and attention. However, the effects of ␤-lactolin on brain inflammation in AD have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accumulating evidence [16,17] indicates that supplementation with whey digestion rich in ␤-lactolin improves memory retrieval and attention. However, the effects of ␤-lactolin on brain inflammation in AD have not been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…␤-Lactolin has been shown to increase monoamine levels in the frontal cortex and hippocampus and improve spatial working memory and attention in pharmacologically induced amnesia mice. Our previous studies showed that supplementation with ␤-lactolin-rich whey peptides improved memory retrieval, attention, and executive function in healthy adults [16,17], and the findings suggest that consumption of ␤-lactolin-rich whey peptides is associated with activation of the frontal cortex, especially the dorsolateral prefrontal cortex regulating memory retrieval and executive function. However, the effects of ␤lactolin on dementia and cognitive decline remain unclear.…”
Section: Introductionmentioning
confidence: 92%
“…It has been shown that protein hydrolysates are involved in GLP-1 and CCK hormones, indicating that bioactive peptides might be used to control both food intake and body weight management (Geraedts et al, 2011). Furthermore, whey peptide-rich supplementation might improve cognitive function in adults, suggesting that whey peptides might be beneficial for fatigue in adult subjects (Kita et al, 2018). It has been suggested that milk protein supplementation in healthy man leads to increase bone formation and decrease bone resorption in term of urinary markers (Toba et al, 2001).…”
Section: Hydrocolloids and Human Healthmentioning
confidence: 99%
“…In recent years, there has been an increase in interest in whey [ 1 ]. It is a by-product of cheese production and a rich source of exogenous amino acids and biologically active proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Other whey peptides include: immunoglobulins, albumins, lactoferrin and lactoperoxidase [ 3 ]. Due to its varied composition, whey is commonly supplemented to emaciated patients (e.g., during convalescence or cancer cachexia), children with cow’s milk protein allergy and sportsmen to increase their muscle mass [ 1 , 4 ]. Whey proteins are also a valuable source of sulphuric amino acids: cysteine and methionine, crucial for the synthesis of reduced glutathione (GSH) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%